Light Changes: Experiences in the Presence of Transforming Light by Annekatrin Puhle - Sartori, Penny (Journal of Scientific Exploration, 2014)
Author Annekatrin Puhle is a philosopher, health consultant, and psychical researcher in the area of exceptional human experiences. This book is an extensive review of light experiences that have been reported throughout history. In particular, the book focuses on light experiences in which the light described appeared to have a healing potential and a transcendent capacity. The author has undertaken extensive research into amassing and analyzing a multitude of experiences from many different sources. There is an extensive collection of more than 800 examples gleaned from the literature as well as 51 self-selected, word-of-mouth reports collected by the author. All previously reported cases are taken from what the author considers to be classic and potentially classic texts in the field of psychical research and related fields, as well as from three major journals: the Journal of the Society for Psychical Research, PSI Researcher, and Paranormal Review.The book begins with an historical consideration of light experiences throughout the ages in scriptures and ancient texts and in folklore, myths, and cultural beliefs. Light experiences have been described in a variety of contexts such as life-threatening events, crisis, depression, as well as featuring prominently in ancient texts. Such experiences have long-lasting, profound, and life-transforming effects on those who report them.